Dan Peranan Guru Pendidikan Agama Hindu Dan Budi Pekerti Dalam Menanamkan Nilai-Nilai Moderasi Beragama Pada Siswa Di SMP Negeri 1 Denpasar: Peranan Guru, Pendidikan Agama Hindu dan Budi Pekerti, Nilai-Nilai Moderasi Beragama - Saraswati, Wedanti (UHN IGB Sugriwa Denpasar, 2025)
This study examines the role of Hindu religious education and character development teachers in instilling religious moderation values among students at SMP Negeri 1 Denpasar. Religious moderation is a crucial element in shaping an educational environment that is harmonious, tolerant, and free from conflict. This research focuses on three main aspects: 1) The attitude of religious moderation among students at SMP Negeri 1 Denpasar, 2) The role of Hindu religious education and character development teachers in the internalization of religious moderation values, and 3) The impact of instilling religious moderation values on students. The research employs a qualitative descriptive approach with data collection techniques including observation, interviews, literature studies, and documentation. Data analysis is conducted systematically through data reduction, data presentation, and conclusion drawing. The results show that students' attitudes towards religious moderation are reflected in various activities such as social service, deliberations in the election of student council representatives (OSIS), participation in extracurricular activities, and involvement in ceremonies and local cultural performances. Teachers play a central role in instilling religious moderation values by teaching fundamental concepts in Hindu teachings such as Tat Twam Asi, Tri Hita Karana, and Catur Paramitha. The internalization of these values has a positive impact on students, as evidenced by increased solidarity, tolerance, responsibility, appreciation for diversity, and the creation of a safer, more orderly, and conducive school environment for learning. Keywords: The Role of Teachers, Hindu Religious Education and Ethics, Religious Moderation Values